2019
DOI: 10.1016/j.jtho.2019.08.1322
|View full text |Cite
|
Sign up to set email alerts
|

P1.18-06 Efficacy and Safety of Neoadjuvant PD-1 Blockade with Sintilimab in Resectable Non-Small Cell Lung Cancer

Abstract: Background: Ceritinib is a highly selective ALK inhibitor that has been shown potent antitumor activity against ALK-positive nonsmall cell lung cancer (NSCLC). We conducted a multicenter singlearm phase II study to assess the efficacy and safety of neoadjuvant therapy with ceritinib followed by surgery in patients with ALKpositive resectable locally advanced (LA) NSCLC. Method: Three cycles of ceritinib were administered as induction therapy. The drug was administered orally at the dose 750 mg once daily for 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…As a whole, sintilimab has shown good safety profiles in neoadjuvant therapy for resectable NCSLC. Another study by Li et al ( 16 ) also showed that neoadjuvant sintilimab treatment in NSCLC patients was well tolerated, with an MPR of 40.5% and a pCR of 16.2%. A decrease in TMU on PET–CT rather than a change in the sum of lesion diameters (SLD) was also identified as a predictor of pathological response to anti-programmed cell death-1 (PD-1) therapy in early-stage NSCLC in another study.…”
Section: Review and Perspective On Neoadjuvant Therapy With Immune Chmentioning
confidence: 87%
“…As a whole, sintilimab has shown good safety profiles in neoadjuvant therapy for resectable NCSLC. Another study by Li et al ( 16 ) also showed that neoadjuvant sintilimab treatment in NSCLC patients was well tolerated, with an MPR of 40.5% and a pCR of 16.2%. A decrease in TMU on PET–CT rather than a change in the sum of lesion diameters (SLD) was also identified as a predictor of pathological response to anti-programmed cell death-1 (PD-1) therapy in early-stage NSCLC in another study.…”
Section: Review and Perspective On Neoadjuvant Therapy With Immune Chmentioning
confidence: 87%
“…Even if there is a relapse, it will obviously move backwards in time, and it can increase the 5-year survival rate by about 20% [32 ]. It was con rmed ~ as for surgically resectable non-small cell lung cancer, neoadjuvant immunotherapy, high safety does not affect surgery, and the pathological signi cant remission rate is 45%, and the 18-month relapse-free survival rate is 73% [33]. Studies have also shown that early non-small cell cancer administration of immune drugs to block multiple molecular tags can kill cancer cells with fewer side effects [34].…”
Section: A B 4 Discussionmentioning
confidence: 98%
“…For LUAD patients with high immune scores before and after surgery, immunotherapy or combined immunotherapy based on precise gene sequencing can reduce the harm of radiotherapy and chemotherapy. 31 Studies reported that postoperative immunotherapy could generally reduce the local recurrence rate by about 30%, significantly reduce distant metastases, and increase the 5-year survival rate by about 20%. 32 Even if the tumor recurred, the recurrence time could be obviously delayed.…”
Section: Discussionmentioning
confidence: 99%
“…For LUAD patients with high immune scores before and after surgery, immunotherapy or combined immunotherapy based on precise gene sequencing can reduce the harm of radiotherapy and chemotherapy. 31 Studies reported that postoperative immunotherapy could generally reduce the local recurrence rate by about 30%, significantly reduce distant metastases, and increase the 5-year survival rate by 32 Even if the tumor recurred, the recurrence time could be obviously delayed. 32 It was confirmed that for treating the resectable non-small cell lung cancer, neoadjuvant immunotherapy was highly safe and did not affect surgery, with 45% of the pathologically significant remission rate and 73% of the 18-month recurrence-free survival rate.…”
mentioning
confidence: 99%